Therapeutic Effect of Liquiritin Carbomer Gel on Topical Glucocorticoid-Induced Skin Inflammation in Mice - Yun Zhang; Sijia Li; Yanfang Huang; Congjing Song; Weiqiang Chen; Yiling Yang (Pharmaceutics, 2024)
Glucocorticoids are often used and highly effective anti-inflammatory medications, but prolonged topical application may alter the epidermis’ normal structure and function, potentially resulting in a number of adverse effects. Topical glucocorticoid-induced skin inflammation is a dangerous condition that develops after topical glucocorticoid use. The patients become dependent on the medication and, even after the medication is stopped, the dermatitis symptoms recur, severely impairing their quality of life. Thus, the need to aggressively confront Topical glucocorticoid-induced skin inflammation is critical. Prior research has demonstrated that topical administration of licorice’s flavonoid component liquiritin stimulates epidermal proliferation, which in turn enhances the creation of collagen and the healing of wounds. Therefore, the purpose of this work was to determine if topical use of liquiritin carbomer gel can treat glucocorticoid-induced changes in mice skin epidermal function, and the mechanisms involved. The findings demonstrated that, in the mice model of topical glucocorticoid-induced skin inflammation, liquiritin carbomer gel aided in the restoration of skin barrier function. These outcomes may have been caused by enhanced expression of the proteins Aquaporin 3, Keratin 10, and Claudin-1, as well as the restoration of epidermal hyaluronan content. In the meantime, liquiritin carbomer gel dramatically decreased the expression of TNF-α, IL-1β, IL-6, IFN-γ, and IgE in mice, according to ELISA tests. Furthermore, topical treatment of liquiritin carbomer gel boosted the expression of superoxide dismutase, catalase, and decreased malondialdehyde expression, potentially counteracting the detrimental effects of glucocorticoids on the epidermis. In summary, these findings imply that topical liquiritin carbomer gel can treat glucocorticoid-induced skin damage through various mechanisms of action.